A reference genome of the Chinese hamster based on a hybrid assembly strategy. Issue 8 (29th May 2018) - Rupp, Oliver; MacDonald, Madolyn L.; Li, Shangzhong; Dhiman, Heena; Polson, Shawn; Griep, Sven; Heffner, Kelley; Hernandez, Inmaculada; Brinkrolf, Karina; Jadhav, Vaibhav; Samoudi, Mojtaba; Hao, Haiping; et al.
Abstract: Accurate and complete genome sequences are essential in biotechnology to facilitate genome‐based cell engineering efforts. The current genome assemblies for Cricetulus griseus, the Chinese hamster, are fragmented and replete with gap sequences and misassemblies, consistent with most short‐read‐based assemblies. Here, we completely resequenced C. griseus using single molecule real time sequencing and merged this with Illumina‐based assemblies. This generated a more contiguous and complete genome assembly than either technology alone, reducing the number of scaffolds by >28‐fold, with 90% of the sequence in the 122 longest scaffolds. Most genes are now found in single scaffolds, including up‐ and downstream regulatory elements, enabling improved study of noncoding regions. With >95% of the gap sequence filled, important Chinese hamster ovary cell mutations have been detected in draft assembly gaps. This new assembly will be an invaluable resource for continued basic and pharmaceutical research. Abstract : The authors completely resequenced the Chinese hamster genome using Single Molecule Real Time (SMRT) sequencing and merged the resulting SMRT‐based assembly with the publicly available draft Illumina‐based assemblies. The new assembly is more contiguous and complete than genome assemblies from either technology alone, reducing the number of scaffolds by >28‐fold, with 90% of the sequence in the 122 longest scaffolds. This new assembly will be an invaluable resource for continued basic and pharmaceutical CHO cell research.